Instrumen Perhatian Orang Tua dan Instrumen Perilaku Menyimpang Siswa SMP - Nuzila, Isna; Sancaya, Setya Adi; Ningsih, Risaniatin (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2021)
This study aims to realize the psychological scale of parental attention and student deviant behavior at school. This research was conducted with the consideration that data on parental attention and student deviant behavior in schools is very necessary for guidance and counseling teachers in providing guidance and counseling services, besides that it is also useful for research activities. When at home has a relationship with student deviant behavior at school. To determine the level of parental attention and the level of student deviant behavior in junior high school, an instrument is needed in the form of a psychological scale of parental attention and deviant behavior of junior high school students. The procedure for developing a psychological scale was carried out briefly to determine the validity and reliability of the psychological scale of parental attention and the instrument of deviant behavior for junior high school students. Based on calculations using product-moment correlation and Cronbach's alpha, the results for the parental attention instrument 56 items were declared valid with reliability of 0.921 and in the high category. Furthermore, for the instrument of student deviant behavior, 35 statement items were declared valid with reliability of 0.902. The conclusion of this study is that the final product in the form of a psychological scale of parental attention and student deviant behavior in schools is valid and reliable.